Investment and Cash Flow: New Evidence - Lewellen, Jonathan; Lewellen, Katharina (Journal of Financial and Quantitative Analysis, 2016)
We study the investment–cash flow sensitivities of U.S. firms from 1971–2009. Our tests extend the literature in several key ways and provide strong evidence that cash flow explains investment beyond its correlation with q . A dollar of current- and prior-year cash flow is associated with $0.32 of additional investment for firms that are the least likely to be constrained and $0.63 of additional investment for firms that are the most likely to be constrained, even after correcting for measurement error in q . Our results suggest that financing constraints and free-cash-flow problems are important for investment decisions.